Propuesta de planificación territorial urbana como escenario de la movilidad cotidiana, a partir del estudios de nodos en Resistencia (Chaco, Argentina) - Rey, Celmira Esther (2015)
A spatial planning refers to the need to build priority guidelines to be implemented in a particular social context, without forgetting the existing legislative framework of the Government State.This paper gives some proposals to improve current conflicts of daily mobility in Resistance mainly those related to the structure and urban network, in terms of its functionality, articulation and readability. The study is based on sustainability principles related to environmental guidelines, universal accessibility and the right to the city. This includes the existence and implementation of protective components and caring attitudes in the public road. The content of the proposal is aimed at analyzing the interrelationships: territory - population movements, describing their current situation and, wielding guidelines governing the organization of local space. It suggest the definition of public policies that prioritize actions closest to the events, as part of a process that requires the implementation of a collaborative work, between government agencies and stakeholders interested in the topic.